2020
DOI: 10.1038/s41392-020-0126-x
|View full text |Cite
|
Sign up to set email alerts
|

WIP1 promotes cancer stem cell properties by inhibiting p38 MAPK in NSCLC

Abstract: Cancer stem cells (CSCs) are a small population of stem cell-like cancer cells that can initiate tumors in vivo, and are the major source of cancer initiation, relapse, and drug resistance. We previously reported that the p38 MAPK, through its downstream effectors MK2 and HSP27, suppressed CSC properties by downregulating the expression of transcription factors that mediate stemness in non-small-cell lung cancer (NSCLC) cells, and that despite unaltered total expression of total p38 proteins, the levels of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 42 publications
(63 reference statements)
0
15
0
Order By: Relevance
“…Similarly, inhibition or loss of WIP1 did not increase the level of p38 activation after UVC or other forms of stress. Most of the studies describing the effect of WIP1 on p38 pathway relied on shRNA‐mediated depletion of WIP1 in the stable cell lines or on prolonged treatment with WIP1 inhibitor [40]. For instance, Deng et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, inhibition or loss of WIP1 did not increase the level of p38 activation after UVC or other forms of stress. Most of the studies describing the effect of WIP1 on p38 pathway relied on shRNA‐mediated depletion of WIP1 in the stable cell lines or on prolonged treatment with WIP1 inhibitor [40]. For instance, Deng et al .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Deng et al . [40] reported that treatment of A549 cells with GSK2830371 for 24–48 h increased the level of active p38. In the short treatment with an efficient dose of GSK2830371, we did not observe any effect on the basal level of active p38.…”
Section: Discussionmentioning
confidence: 99%
“…The protein phosphatase WIP1 (PPM1D) inhibitors are currently under clinical evaluation for their capability to subtract p53 from proteolytic degradation or inactivation. Deng et al (2020a) described a novel function of the WIP1 inhibitor GSK283071, which suppresses stemness features in NSCLC through the activation of p38 MAPK. Specifically, the inhibition of WIP1 induced p38 MAPK phosphorylation and consequent activation of the downstream targets MK2 and HSP27 and reduction of the SOX2, OCT4, NANOG and ALDH1A1 stemness markers, sphere forming capability and tumor-initiating potential (Deng et al, 2020a).…”
Section: Kinases and Phosphatases As Therapeutic Targets In Cancer Stem Cellsmentioning
confidence: 99%
“…Recently, numerous studies have confirmed that HspB1 phosphorylation/dephosphorylation is a critical regulator in the formation/maintenance of CSC properties. HspB1 undergoes phosphorylation as the terminal substrate in the p38/MAPK pathway, and there are increasing reports linking this p38 MAPK/MAPKAPK2/HSP27 pathway to chemoresistance in lung CSCs [128,131] and oral CSCs [138], maintenance of CSC properties in lung CSCs [131], and EMT in renal [143] and lung CSCs [139]. Similarly, in colorectal CSCs, protein phosphatase PP2A was reported to dephosphorylate HspB1 and attenuate HspB1 effects by promoting CSC properties [136,144], indicating that the status of phosphorylated HspB1, mediated by kinase and phosphatase, is essential for HspB1 effects on CSC properties.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
“…Then, HspB1 was identified to be related to CSC stemness by proteomics [ 129 ]. Indeed, several studies have shown that HspB1 is essential for CSC stemness in salivary adenoid cystic carcinoma [ 130 ], non-small-cell lung cancer [ 131 ], and breast cancer [ 132 ]. There are also reports linking HspB1 to the maintenance of CSC phenotypes in breast cancer stem cells [ 133 ] and gynecologic cancer stem cells [ 134 ].…”
Section: Functions Of Small Heat Shock Proteins In Cancersmentioning
confidence: 99%